Breaking bad news of cancer diagnosis – Perception of the cancer patients in a rural community in Malaysia - Bain, Mathew Gabriel; Cheah, W.L; Chang, C.T (Wolters Kluwer, 2014)
Context: Breaking of bad news is an important component in the management of cancer patients. Aims: This study aimed to assess the perceptions of breaking bad news of cancer diagnosis. Settings and Design: It was a cross‑sectional study using Breaking Bad News Assessment Schedule (BAS) questionnaire on cancer patients in Serian district. Materials and Methods: Using snowballing sampling method, a total of 134 patients were interviewed face‑to‑face after the consent was obtained from each of the respondents. Statistical Analysis Used: Data was entered and analyzed using SPSS version 19.0. Results: Majority were comfortable with the current method of breaking bad news. The main aspects found to be the areas of concern were the importance of the usage of body language, management of time and identifying patients’ key area of concerns. There were significant difference between sex and “information giving” (P = 0.028) and “general consideration” (P = 0.016) and also between “the age and setting the scene” (P = 0.042). Significant difference was also found between the types of cancer and “the setting of scene” (P = 0.018), “breaking bad news technique” (P = 0.010), “eliciting concerns” (P = 0.003) and “information giving” (P = 0.004). Conclusion: Good and effective communication skill of breaking bad news is vital in the management of cancer patients. As the incidence of new cases of cancer increase every year, breaking of bad news has become a pertinent to the medical professionals’ role. Specific aspects of communication skills based on local characteristics should be more emphasized in the formulation of training for doctors.